Pretransplant assessment of cyclosporine level as a predictor of cyclosporine dose requirements after kidney transplantation - Sahier O El-Khashab; Amin R Soliman; Rabab M Ahmed; Samar Amin (SpringerOpen, 2019)
Introduction and aims Pretransplant administration of cyclosporine (CsA) may reduce post-transplant maintenance dose and consequently CsA inhibitor nephrotoxicity and helps in achieving the desired target C2 levels earlier. The optimum dose or timing of administration of CsA induction dose is still debatable. Patients and methods We compared three different protocols for pretransplant administration of CsA aiming to reach a target C2 therapeutic level of greater than 800 ng/ml on the third day post-transplant. Sixty kidney transplant recipients from Cairo University hospitals were divided into: group 1 (n=20) who received a single CsA induction dose of 2 mg/kg 12 h pretransplant; group 2 (n=20) who received four CsA consecutive doses of 4 mg/kg 48 h pre-transplant; and group 3 (n=20) who received four CsA consecutive doses of 2 mg/kg 48 h pretransplant. Results The desired therapeutic level in the earlier post-transplantation period was achieved in 65% in group 1, 100% in groups 2 and 3). In group 2 a lower dose was needed to maintain C2 within the therapeutic range during the first year post-transplantation (P<0.01). Furthermore, a lower number of cases were complicated by CsA nephrotoxicity in group 2 in comparison to groups 1 and 3 (25, 0, 5% in group 1, 2, 3, respectively, P<0.039). A higher longer dose of CsA pretransplant associated with early withdrawal of CsA had a better effect on graft function than lower or shorter induction doses with late withdrawal as evidenced by lower serum creatinine levels all through the follow-up period in group 2 compared with group 3. Conclusion Forty-eight-hour pretransplant induction with CsA at a dose of 4 mg/kg with early dose reduction post-transplant was associated with lower CsA maintenance and a better 1-year graft function.